2023
DOI: 10.1128/spectrum.03588-22
|View full text |Cite
|
Sign up to set email alerts
|

PorinPredict: In Silico Identification of OprD Loss from WGS Data for Improved Genotype-Phenotype Predictions of P. aeruginosa Carbapenem Resistance

Abstract: Pseudomonas aeruginosa is a major cause of multidrug-resistant nosocomial infections. The emergence and spread of clones exhibiting resistance to carbapenems, a class of critical last-line antibiotics, is therefore closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…[ 52 ]. The functionality of the outer-membrane porin oprD was analyzed in silico using the recently described PorinPredict tool [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 52 ]. The functionality of the outer-membrane porin oprD was analyzed in silico using the recently described PorinPredict tool [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have shown that inactivation of OprD due to mutations inside the open reading frame (ORF) and reduced expression of OprD due to mutations in the promoter or its regulators are frequently observed in clinical P. aeruginosa isolates (Biggel et al., 2023 ; Sherrard et al., 2022 ; Shu et al., 2017 ). Inactivation of OprD contributes significantly to the carbapenem resistance of P. aeruginosa .…”
Section: Porins In P Aeruginosamentioning
confidence: 99%
“…A potential solution for the latter problem is to move beyond phenotypic (growth-based) susceptibility testing, and to use bacterial whole genome sequences (WGS) to infer antimicrobial susceptibility (38)(39)(40)(41)(42). However, most WGS-based approaches focus on finding known resistance mechanisms and while they are successful in that, identifying (combinations of) mutations in one or more genes not previously associated with reduced susceptibility, and incorporating these in a prediction algorithm, remains a major challenge (43).…”
Section: Genomic Detection Of Resistance Mechanismsmentioning
confidence: 99%